Makna Lirik Sawer Sunda (Sawer Penganten) Rajah Sawer Penganten Pada Acara Pernikahan Adat Suku Sunda - Manalu, Erika; Torang Naiborhu; Vanesia Amelia Semayang (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
Sawer Penganten (Sundanese Sawer) is a cultural practice of the Sundanese people. The Sundanese tribe, originally from Java, migrated to Medan, a city characterized by its ethnic diversity. This diversity enriches the cultural landscape of Medan. This research explores the significance of the lyrics of Sawer Sunda (Sawer Penganten) within the context of wedding ceremonies in Medan. The primary focus of this study is to analyse the meaning of the Sawer Sunda lyrics (Sawer Penganten) in this urban setting. To conduct this analysis, the author employs Ferdinand de Saussure's theory. A qualitative research methodology is utilized to gather and collect data. Qualitative research is fundamentally naturalistic, as described by Dr. H. Zuchri Abdussammad, and is conducted in the field. The author undertook observations, interviews, and captured photographs or videos for data collection purposes. The findings of this study indicate that Sawer Sunda (Sawer Penganten) is a significant wedding custom among the Sundanese, serving as a means for parents to impart their advice to the bride and groom. The Sundanese events held in Medan maintain the philosophical values inherent to the Sundanese tribe's region of origin.